A Case Report of a Primary Small Cell Carcinoma of the Subglottis - Ahmayuddin, Hazeem; Khalid, Jamsari (Trinity Student Medical Journal, 2020)
Small cell carcinoma (SmCC) is a type of cancer affecting the subglottic region of the larynx.Subglottic carcinomas represent only less than 5% of laryngeal cancers, with SmCC accounting for only 0.5%. This case report highlights a patient with a rapidly-progressing laryngeal growth that caused a significant airway obstruction within a period of three weeks. Further investigation revealed that the patient was suffering from a rare form of laryngeal neoplasm, which was consistent with a diagnosis of a limited stage primary SmCC of the subglottis. He was then started on a regimen of radiotherapy with concomitant chemotherapy (cisplatin and etoposide) for a duration of two months. Response to therapy was rapid, with a reduction in tumour size. A combination of radiotherapy and platinum-based chemotherapy is currently the modality of choice for treatment, with recent data showing that surgery has a limited role in laryngeal SmCC.